2004
DOI: 10.1093/ajcn/80.2.337
|View full text |Cite
|
Sign up to set email alerts
|

No difference in body weight decrease between a low-glycemic-index and a high-glycemic-index diet but reduced LDL cholesterol after 10-wk ad libitum intake of the low-glycemic-index diet

Abstract: This study does not support the contention that low-fat LGI diets are more beneficial than HGI diets with regard to appetite or body-weight regulation as evaluated over 10 wk. However, it confirms previous findings of a beneficial effect of LGI diets on risk factors for ischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
181
3
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(198 citation statements)
references
References 44 publications
10
181
3
4
Order By: Relevance
“…In one study, high-carbohydrate diets were linked to accelerated atherosclerosis progression, and high GI carbohydrates were particularly harmful (Mozaffarian et al, 2004). In experimental studies, high GI and GL diets have been documented to have adverse effects on cardiovascular risk factors, such as triglyceride concentrations, low-density lipoprotein cholesterol, the ratio of total to high-density lipoprotein cholesterol and C-reactive protein (Ludwig, 2002;Pereira et al, 2004;Sloth et al, 2004;McMillan-Price et al, 2006). Because these risk factors are associated with worse prognosis among patients with established cardiovascular disease (Smith et al, 2006), we hypothesized that diets high in GI and GL may be associated with increased total and cardiovascular mortality in patients with existing cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, high-carbohydrate diets were linked to accelerated atherosclerosis progression, and high GI carbohydrates were particularly harmful (Mozaffarian et al, 2004). In experimental studies, high GI and GL diets have been documented to have adverse effects on cardiovascular risk factors, such as triglyceride concentrations, low-density lipoprotein cholesterol, the ratio of total to high-density lipoprotein cholesterol and C-reactive protein (Ludwig, 2002;Pereira et al, 2004;Sloth et al, 2004;McMillan-Price et al, 2006). Because these risk factors are associated with worse prognosis among patients with established cardiovascular disease (Smith et al, 2006), we hypothesized that diets high in GI and GL may be associated with increased total and cardiovascular mortality in patients with existing cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several ad libitum trials conducted on nondiabetic subjects have suggested a beneficial effect of low-GI diet on fat mass (Bouche et al, 2002) and body weight (Bouche et al, 2002;Sloth et al, 2004), when compared with high-GI diet, although other trials conducted on subjects with type II diabetes have found no differences in body weight change between high-and low-GI diets (Heilbronn et al, 2002;Jimenez-Cruz et al, 2003;Rizkalla et al, 2004). Additionally, although there has been no association between dietary GI and GL and BMI in some studies (Amano et al, 2004;Liese et al, 2005), other observational studies have shown a positive association between dietary GI, but not dietary GL and BMI Murakami et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intake of dietary fiber (unavailable carbohydrate) has been shown to be independently negatively associated with a measure of obesity in several (Appleby et al, 1998;Ludwig et al, 1999;Liu et al, 2003;Sasaki et al, 2003;Spencer et al, 2003;Howarth et al, 2005;Liese et al, 2005), but not all (Stookey, 2001), observational studies. Although high dietary fiber intake is often correlated with low dietary GI and/or GL (Howarth et al, 2001;Bouche et al, 2002;Scholl et al, 2004;Schulze et al, 2004;Sloth et al, 2004;Schulz et al, 2005), few observational studies have examined these dietary factors simultaneously in relation to a measure of obesity, especially in non-Western populations (Toeller et al, 2001;Amano et al, 2004;Sahyoun et al, 2005). Clearly, additional studies are needed on the effects of these dietary factors on the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Genetically predisposed children might be more vulnerable to the unfavourable metabolic consequences of consuming high-GI foods, whereas normal children may not gain weight when subjected to the same high glycaemic load. In view of the fact that some intervention studies in children have found an increase in satiety and a reduction in food consumption after lowering the glycaemic load of meals (Spieth et al, 2000;Warren et al, 2003), and beneficial outcome has also been observed in intervention studies in adults (Wolever and Mehling, 2003;Sloth et al, 2004), more long-term intervention studies are needed to delineate the potential causal relationship between GI and obesity in childhood.…”
Section: Discussionmentioning
confidence: 99%